Pilot Study on the Vibration Behavior of TCC Laminated Deck Systems - Mat Gamadi, Nur Emilia; Abd Ghafar, Nor Hayati; Eng Chuan, David Yeoh; Rahimi, Muhammad Imran; Abd Aziz, Nur Azmina (International Journal of Integrated Engineering, 2021)
The timber concrete composite (TCC) deck system is a new technology that consists of timber and concrete composite structures but remains uncommon in Malaysia. TCC is a structural system where timber beams and concrete slabs are combined to form a composite material, resisting tensile stress and compressive stress, respectively. The addition of concrete slabs protects timber beams from direct contact with water, which is crucial to ensure the durability of timber beams. Different types of connectors can be used to provide force exchange between concrete slabs and timber beams. This research was conducted to study the vibration behavior of timber-concrete composite deck systems with or without concrete topping. The deck was constructed using twenty pieces of sawn timber measuring 3.6m x 0.09 m with a concrete topping of 0.065m. Experimental tests were conducted using an electrodynamic shaker with a frequency range of 1 Hz to 200 Hz. The shaker was placed on a laminated deck as vertical force and 15 accelerometers were used as output data collectors. MeÂ´scope and SAP2000 package were used for data analysis. The natural frequency values of the first mode shape with and without concrete topping based on MeÂ´scope analysis are 12.8Hz and 16.9Hz, respectively. Meanwhile, the finite element modeling analysis shows that the frequency of the first mode shape with laminated deck without concrete topping is 11.4 Hz while the one with concrete topping is 16.2 Hz. The natural frequencies obtained from the experimental test and the modal analysis are greater than 8 Hz, thereby concluding that the TCC laminated deck system is suitable and comfortable for building occupants.